Comparative Analysis of Kakawin Sutasoma and The Short Story “Kepergian Sutasoma” By Gunawan Maryanto - Janah, Nadia Mawar (CV. Publikasi Indonesia, 2025)
This study compares Kakawin Sutasoma by Mpu Tantular with the short story